Acquired torticollis due to primary pyomyositis of the paraspinal muscles in an 11-year-old boy. (18th March 2016) - Ray, S; Iyer, A; Avula, S; Kneen, R
Abstract : Torticollis is characterised by tilting and rotation of the cervical spine in opposite directions. Causes can be congenital or acquired. Primary pyomyositis is a rare subacute deep bacterial infection of skeletal muscles that typically affects individuals under 20 years of age from tropical countries. Infrequently, pyomyositis occurs in individuals from temperate regions, usually in immunocompromised adults, and this is defined as secondary pyomyositis. We report a case of acquired torticollis due to primary pyomyositis of the paraspinal muscles in a previously healthy boy from the UK. A prolonged course of antibiotics and physiotherapy led to a complete resolution of his illness. We review how to differentiate pyomyositis from focal myositis, a more common inflammatory muscular cause of acquired torticollis.